THE INFLUENCE OF BRAND IDENTITY TOWARDS BRAND LOYALTY AND RESILIENCE TO NEGATIVE INFORMATION ON HONDA IN JAKARTA - UTOMO, ALEXANDER PRIMA; PRASASTYO, KLEMENS WEDANAJI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This research aims to determine the influence of service quality, price and restaurant environment variables on customer loyalty through customer satisfaction variables. The object of this research is the China restaurant